Duration of Efficacy Increases with the Repetition of Botulinum Toxin A Injections in Primary Axillary Hyperhidrosis: A 15-year Study in 117 Patients - Clémence Berthin; Hervé Maillard (Medical Journals Sweden, 2019)
Changes in the duration of efficacy of botulinum toxin A injections for primary axillary hyperhidrosis have not been studied in depth. The aim of this study was to assess such changes. In a retrospective cohort of 220 patients, seen over a 17-year period, duration of efficacy was recorded, including duration of efficacy of first and last injections. Of 220 patients, 117 fulfilled the study criteria (79 females and 38 males, age 17-79 years, mean age 38.3 years). Patients received 3-24 injections (mean 5.5). The duration of efficacy of the first injections was 3 weeks to 30 months (median 6 months), and the duration of efficacy of the final injections was 3 weeks to 66 months (median 8 months) (p < 0.001). An increase in duration of efficacy occurred in 62% of patients with repeated injections. Of the 20 patients with a follow up >10 years, the mean number of treatments was 8.25/patient; in 18 of these patients the duration of efficacy increased by > 50%. In conclusion, repeated botulinum toxin A injections lead to an increase in duration of efficacy without secondary decrease.